(untitled) ("Temas Sociais" Journal, 2025)
The COVID-19 pandemic has had a global social, economic, cultural and political impact, particularly on the most vulnerable groups. In the Social Work profession, covid-19 has triggered a restructuring of practices, with new challenges emerging in the field of intervention. This article seeks to analyze Social Work practices in response to the covid-19 pandemic in Loures, starting with an analysis of the causes and effects of the covid-19 pandemic, the policies and measures adopted in response to the pandemic, as well as Social Work practices in the Loures Social Assistance and Support Service. This municipality was chosen because Loures was one of the municipalities in the Lisbon Metropolitan Area most affected by covid-19, with a need to implement the public health and social support model, given the incidence of transmission chains of the virus. The practices unleashed at the Loures SAAS showed the profession’s capacity for reinvention, the service provided in an organized manner through networking, resulting in successful intervention in response to the pandemic.